1985
DOI: 10.26749/rstpp.119.7
|View full text |Cite
|
Sign up to set email alerts
|

Mammals of the Upper Henty River Region, Western Tasmania

Abstract: A mammal survey was conducted in the Upper Benty River Region in western Tasmania. The area had been subject to much disturbance from mining, forestry and frequent fires and was covered by a maze of roads and tracks. Nineteen native species (including bats) were recorded. Four of the species listed in 1983 as occurring in the Lower Gordon Region, 80 km south of the present study area, were not recorded during our survey. It is considered that three of these species would probably have been found in the area wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…2019 a , 2019 b ). Our results confirmed that P. tridactylus is able to utilise a broader range of vegetation communities than is B. gaimardi , including vegetation types in areas of high rainfall (Rose and Rose 1998), such as rainforest (Taylor et al . 1985).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…2019 a , 2019 b ). Our results confirmed that P. tridactylus is able to utilise a broader range of vegetation communities than is B. gaimardi , including vegetation types in areas of high rainfall (Rose and Rose 1998), such as rainforest (Taylor et al . 1985).…”
Section: Discussionsupporting
confidence: 82%
“…B. gaimardi may be able to utilise disturbed landscapes, whereas P. tridactylus may not (Gardiner et al 2019a(Gardiner et al , 2019b. Our results confirmed that P. tridactylus is able to utilise a broader range of vegetation communities than is B. gaimardi, including vegetation types in areas of high rainfall (Rose and Rose 1998), such as rainforest (Taylor et al 1985).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, there have been several regional bat trapping surveys. Taylor and O'Neill (1986) surveyed bat communities by trapping in five forest habitats in south-east Tasmania, Taylor et al (1985) trapped bats in rainforest and eucalypt scrub in the Upper Henty Region of Western Tasmania, and Schulz and Kristensen (1996) surveyed bats in coastal areas of south-west Tasmania. Duncan (1995) and Rhodes (1996) used ultrasonic detectors to survey bats in eastern and south-eastern Tasmania as part of studies investigating use of silvicultural regrowth.…”
Section: Introductionmentioning
confidence: 99%